Nstar 2004 : (World Scientific, 2004)
This book covers recent advances in the field of nucleon resonances presented at the IX International Workshop on the Physics of Excited Baryons, NSTAR2004. A complete overview of the most recent experimental results obtained worldwide on baryon spectroscopy is presented together with theoretical progress on related topics ranging from resonance parameters extraction to lattice-QCD calculations through effective field theory. Of particular interest, a large part of the book is devoted to exotic states with quantum numbers of pentaquarks, whose recent discovery represents a new chapter in hadronic physics.